Index Card Match Learning Model Integrated with Flipped Classroom to Improve Conceptual Understanding - Swasti, Awidhia Wandi Puri; Budiyanto, Mohammad; Purnomo, Aris Rudi (Jurnal Pendidikan MIPA, 2022)
This research aimed at improving students' conceptual understanding of the excretory system through index card match learning model (ICMLM) integrated with the flipped classroom. This study conducted a pre-experimental with One Group Pre-test-Post-test Design involving 16 students of Junior High School Muhammadiyah 7 Gresik grade VIII within a-twice meeting during limited face-to-face learning. The instruments consisted of pre-test and post-test, learning observation sheets, and questionnaires for student responses. Data collection used test and questionnaire method. Cognitive data analysis of concept understanding using t-test and N Gain. The t-test result obtained a score of 0.000. Besides, the N-Gain test revealed an average score of 0.75, characterized in the high category. This test showed that students' understanding of concepts in detail is increased, namely, 7 students in the medium category and 9 students in the high category. Student responses after treatment were considered very good, with a percentage of 86.45%. Keywords: concept understanding, flipped classroom, index card match learning model. DOI: http://dx.doi.org/10.23960/jpmipa/v23i2.pp505-518